Synthesis of N-TiO2 Effect of the Concentration of Nitrogen in the Band Gap - Pérez, Eliana Guadalupe (2015)
In this work TiO2 modified with nitrogen was synthesized by sol-gel method from the hydrolysis of titanium isopropoxide with urea solution in different concentrations so that the theoretical N/Ti molar ratio was equal to 0, 0.5, 1 and 2, calcined at 400 °C. The samples were characterized by diffuse reflectance spectroscopy, thermo differential analysis and Raman spectroscopy. The TiO2 synthesized without nitrogen are active only under ultraviolet radiation, while samples containing nitrogen absorbed in the visible range. In Raman spectra the characteristic peaks of the crystalline anatase phase were observed with a slight shift and a decrease of the crystallization grade with the increase of the N/Ti ratio. The analysis of photoactivity of the modified catalyst in the degradation of tartrazine under visible light is analyzed.